Family bonds of institutionalized elderly (Research, Society and Development, 2021)
Introduction: Aging is a multidimensional stage in human life, as it assumes dimensions that go beyond the biological cycle, causing emotional and social consequences. All these changes have an impact on the life of the aging individual, especially in the family, which the family undergoes changes and sometimes cannot meet their needs, making the elderly more conducive to social isolation, as well as hospitalization in Long-Term Institutions for the Elderly (LTIEs). Objective: To describe the family ties of the elderly in a Long Term Care Institution for the Elderly in Maceió / AL. Method: This study takes a qualitative approach, cross-sectional and descriptive. For data collection, an interview guided by a semi-structured script was conducted with 10 elderly residents of an LTCF in Maceió / AL. For data interpretation, Bardin's content analysis technique was used, which allowed the identification of three categories: “Family relationship”, “Option for institutionalization” and “Aspects that led them to live at the LTCF”. Results: It was identified that the family relationship after the institutionalization process is relatively fragile or does not maintain it, regarding the option for institutionalization, it is a large part of the family, it was also verified that as for the aspects that led them to live at the LTCF, the disease appeared as the main factor. Conclusion: The results call attention to the need for greater support from the family, since the same when effective, brings with it well-being, which is essential for a good quality of life for the elderly.